Floristic richness and diversity of Bintuni mangrove, Bird's Head Peninsula, West Papua, Indonesia - PETRUS KASIHIW; RONI BAWOLE; JONNI MARWA; AGUSTINUS MURDJOKO; ALEXANDER WIHYAWARI; YUNO HEIPON; REINARDUS LIBORIUS CABUY; NITHANEL MIKAEL HENDRIK BENU; FRANCINE HEMATANG (Society for Indonesian Biodiversity, 2023)
Abstract. Kasihiw P, Bawole R, Marwa J, Murdjoko A, Wihyawari A, Heipon Y, Cabuy RL, Benu NMH, Hematang F. 2023. Floristic richness and diversity of Bintuni mangrove, Bird's Head Peninsula, West Papua, Indonesia. Biodiversitas 24: 2887-2897. Mangrove ecosystems play an important role in the functions of coastal protection, fish and other living-organism habitats, carbon storage, and the livelihood of local people. Yet, mangrove forests generally face ecological threats like anthropogenic pressures. However, fewer studies were carried out in this area, so this research aimed to reveal the vegetation diversity and richness in Bintuni, not only the true mangroves but also the mangroves associates with three different conditions, namely sandy areas called protection forests, disturbed forests called production forests, and delta called nature reserve. The results showed that species vegetation in the Bintuni Mangrove could be differentiated as true mangroves (29.82%) and mangrove associates (70.18%) of the total species richness of mangrove vegetation where in terms of taxonomic composition, the three forests encompassed 25 families, 47 genera, and 57 species clustered into 9 lifeforms. Then, the vegetation diversity and richness were highest in the nature reserve, and 34 (59.65% of total species number) species of vegetation in common share in three forest types. Consequently, frequent checking of vegetation richness is important since the Bintuni mangrove does not seem to have a significant threat like massive conversion of mangrove.